CD81 suppresses NF-κB signaling and is downregulated in hepatitis C virus expressing cells - Maximilian Bunz; Mona Eisele; Dan Hu; Michael Ritter; Julia Kammerloher; Julia Kammerloher; Sandra Lampl; Michael Schindler (Frontiers in Cellular and Infection Microbiology, 2024)
The tetraspanin CD81 is one of the main entry receptors for Hepatitis C virus, which is a major causative agent to develop liver cirrhosis and hepatocellular carcinoma (HCC). Here, we identify CD81 as one of few surface proteins that are downregulated in HCV expressing hepatoma cells, discovering a functional role of CD81 beyond mediating HCV entry. CD81 was downregulated at the mRNA level in hepatoma cells that replicate HCV. Kinetics of HCV expression were increased in CD81-knockout cells and accompanied by enhanced cellular growth. Furthermore, loss of CD81 compensated for inhibition of pro-survival TBK1-signaling in HCV expressing cells. Analysis of functional phenotypes that could be associated with pro-survival signaling revealed that CD81 is a negative regulator of NF-κB. Interaction of the NF-κB subunits p50 and p65 was increased in cells lacking CD81. Similarly, we witnessed an overall increase in the total levels of phosphorylated and cellular p65 upon CD81-knockout in hepatoma cells. Finally, translocation of p65 in CD81-negative hepatoma cells was markedly induced upon stimulation with TNFα or PMA. Altogether, CD81 emerges as a regulator of pro-survival NF-κB signaling. Considering the important and established role of NF-κB for HCV replication and tumorigenesis, the downregulation of CD81 by HCV and the associated increase in NF-κB signaling might be relevant for viral persistence and chronic infection.